2010
DOI: 10.1177/0193945910371320
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of Three Instruments to Measure Fatigue With Myocardial Infarction

Abstract: The purpose of this study was to evaluate the psychometric properties of three questionnaires to measure fatigue with myocardial infarction. The Fatigue Symptom Inventory Interference Scale, Profile of Moods States Fatigue subscale (POMS-F), and Short Form 36 (SF-36) Vitality Scale were completed during hospitalization (n = 116) and 30 days after hospital admission (n = 49). Moderate to strong correlations were found among each of these fatigue scales and between each fatigue scale and measures of other variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
1
13
0
1
Order By: Relevance
“…Hence, this study adds to the previous dementia caregiving research a potential way of explaining previous results, mostly found in other populations (e.g. Chida & Steptoe, ; Fink et al, ) and also in caregivers (Vitaliano, Scanlan, Krenz, & Fujimoto, ) concerning the impact of anger on caregivers' physical health, via its influence on caregivers' optimism. It may well be that angry feelings lead to a reduction in one's sense of optimism regarding one's life and circumstances (Puskar et al, ; Remor et al, ; Shifren & Hooker, ), including expectations and cognitions about one's illnesses, which in turn are related to perceived decline in vitality (Fink et al, ).…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Hence, this study adds to the previous dementia caregiving research a potential way of explaining previous results, mostly found in other populations (e.g. Chida & Steptoe, ; Fink et al, ) and also in caregivers (Vitaliano, Scanlan, Krenz, & Fujimoto, ) concerning the impact of anger on caregivers' physical health, via its influence on caregivers' optimism. It may well be that angry feelings lead to a reduction in one's sense of optimism regarding one's life and circumstances (Puskar et al, ; Remor et al, ; Shifren & Hooker, ), including expectations and cognitions about one's illnesses, which in turn are related to perceived decline in vitality (Fink et al, ).…”
Section: Discussionsupporting
confidence: 56%
“…Chida & Steptoe, ; Fink et al, ) and also in caregivers (Vitaliano, Scanlan, Krenz, & Fujimoto, ) concerning the impact of anger on caregivers' physical health, via its influence on caregivers' optimism. It may well be that angry feelings lead to a reduction in one's sense of optimism regarding one's life and circumstances (Puskar et al, ; Remor et al, ; Shifren & Hooker, ), including expectations and cognitions about one's illnesses, which in turn are related to perceived decline in vitality (Fink et al, ). However, the cross‐sectional nature of the sample precludes us from making any causal direction inferences, and future longitudinal or experimental studies are needed to replicate these data.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations